VOCABULARY MASTERY OF SMAN 4 SOPPENG STUDENTS VIA LEGEND STORYTELLING - A. Adiyah Miftahul Jannah; Samtidar Samtidar; Geminastiti Sakkir (Universitas Negeri Makassar, 2022)
This research aimed to diagnose whether effective or not the students’ mastery of vocabulary via storytelling. The pre-experimental design was the method used by the researchers with one group pre-test and post-test. The population was the second-grade students at SMAN 4 Soppeng in the academic year 2021/2022. This research used a cluster random sampling technique. In this case, the researchers chose XI MIA 1 as the representation of the population which consists of 24 students. The instrument of this research was a vocabulary test administered as a pre-test and post-test. The result of this research proved that there were a significant difference between students‟ scores before treatment and students‟ scores after treatment. It can be seen from the mean score, the mean score of students‟ pre-test was (76.10), which was lower than the mean score of the post-tests (85.13). The significant value of this research (0.001) was smaller than the significant level (0.05). In addition, by doing storytelling the students use some words repeatedly. With repetition, the students can remember the words and also the types of the words. So, it can be concluded that legend storytelling improves students’ vocabulary mastery and is effective in teaching vocabulary at SMAN 4 Soppeng.